Protection Registration Parameters for Legal Protection of Geographical Indication Products Against Combination Factors (Natural Factors with Human Factors) - Apriliani, Kadek; Putu Angga Pratama Sukma; I Made Sudirga (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The research aims to explore the impact of geographical indications on increasing the value of products or commodities, thereby boosting the economy of the region where the geographical indications originate. This focus is directed towards the producers rather than the farmers (protecting the communal society) and adheres to the "first to file" principle, where the party that first applies for registration is prioritized. The study utilizes a normative legal research method, focusing on the lack of norms regarding the parameters for protecting the registration of geographical indications. It appropriately employs the following approaches: statute approach, conceptual approach, and analytical approach. The research emphasizes that the assessment and application of geographical indications with a combination of factors must be fulfilled jointly or consider both natural and human factors influencing the quality characteristics of the produced goods. For instance, potential protection under geographical indications with a combination of factors involves products with main raw materials. The goal is to prevent imitation claiming to be a genuine product in circulation and exploiting geographical indications for the benefit of the rights holder. To ensure beneficial certainty, the geographical indications with a combination of factors require a parameter.